Development of an Augmented Reality Dolanan Song Encyclopedia to Foster Reading Skills in Early Childhood - Febritesna Nuraini Nuraini; Ridhatul Aisy; Junita Dwi Wardhani; Dwi Hastuti; Iyan Sofyan; Santo Mugi Prayitno (Buletin Pengembangan Perangkat Pembelajaran, 2024)
Purpose: This research aims to develop and assess the effectiveness of literacy-based storybooks enhanced with augmented reality (AR) as an intervention for the development of executive functions in early childhood. Executive function is a cognitive ability that underlies tasks such as maintaining focus on long-term goals, delaying gratification, and exercising self-control over impulses. Methodology: The research adopts a 4D development model encompassing four main stages: Define (Definition), Design (Planning), Develop (Development), and Disseminate (Dissemination). This learning medium garnered positive responses from users, with children expressing satisfaction with the appeal of the songs and recognizing the excellence of the 3D pictures and activities in the storybook. The research also evaluates the effectiveness of AR-based encyclopedias in enhancing reading literacy comprehension through pre- and post-test designs. Results: The study revealed an increase in knowledge related to expressing songs. Additionally, there was a modest yet significant improvement in the aspect of responsibility. Children exhibited a greater interest in participating in singing activities with the teacher compared to conventional reading and writing activities.